(MAGMAMagma) [6*Fibonacci(n)*Fibonacci(n+1)+(-1)^n: n in [0..30]];
(MAGMAMagma) [6*Fibonacci(n)*Fibonacci(n+1)+(-1)^n: n in [0..30]];
editing
approved
Let (A), (B) and (C) be sequences of the Fibonacci type, x = {1, 2, ...}, y = {0, 1, ...}. Form the three sequences with the initial values A(0) = x, A(1) = y, B(0) = 7*x - y, B(1) = 5*x, C(0) = A(n), C(1) = B(n). Then a(n) = C(n)/x always applies. - Klaus Purath, Oct 28 2019
From Klaus Purath, Oct 28 2019: (Start)
(a(n-3) - a(n-2) - a(n-1) + a(n))/6 = Fibonacci(2*n-2).
(a(n-5) + a(n))/30 = Fibonacci(2*n-4).
(a(n) - a(n-4))/18 = Fibonacci(2*n-3). (End)
reviewed
editing
proposed
reviewed
editing
proposed
Let (A), (B) and (C) be sequences of the Fibonacci type, x = {1, 2, ...}, y = {0, 1, ...}. Form the three sequences with the initial values A(0) = x, A(1) = y, B(0) = 7*x - y, B(1) = 115*x, C(0) = A(n), C(1) = B(n). Then a(n) = C(n)/x always applies. - Klaus Purath, Oct 28 2019
proposed
editing
editing
proposed
E.g.f.: (1/5)*exp(-x)*(-1 + 6*exp(5*x/2)*(cosh((sqrt(5)*x)/2) + sqrt(5)*sinh((sqrt(5)*x)/2))). - Stefano Spezia, Dec 09 2019
proposed
editing
editing
proposed
a(n) = (a(n-2) - a(n-1) - a(n+1) + a(n+2))/4.